Lipidic cubic phase injector facilitates membrane protein serial femtosecond crystallography - CAFFREY, MARTIN (My University, 2014)
Lipidic cubic phase (LCP) crystallization has proven successful for high-resolution structure determination of challenging membrane proteins. Here we present a technique for extruding gel-like LCP with embedded membrane protein microcrystals, providing a continuously renewed source of material for serial femtosecond crystallography. Data collected from sub-10-μm-sized crystals produced with less than 0.5 mg of purified protein yield structural insights regarding cyclopamine binding to the Smoothened receptor.
PUBLISHED
Keywords: Lipidic cubic phase (LCP)